2018
DOI: 10.3892/or.2018.6757
|View full text |Cite
|
Sign up to set email alerts
|

Berberine induces mitochondrial‑mediated apoptosis and protective autophagy in human malignant pleural mesothelioma NCI‑H2452 cells

Abstract: Increasing evidence shows that berberine has antitumor effects against a number of tumor cells. In the present study, we evaluated the effect of berberine on the proliferation of the human malignant pleural mesothelioma (MPM) cell line NCI-H2452, and explored the therapeutic potential and underlying mechanisms of this agent. Our results showed that berberine inhibited the proliferation of NCI-H2452 cells in a dose-and time-dependent manner and could induce apoptosis, possibly through a caspase-9-dependent intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…In addition, berberine can induce autophagic cancer cell death through increased GRP78 levels and enhancing the binding ability of GRP78 to VPS34 in human colorectal cancer HCT-116 cells [148], whilst it induces autophagy through inhibiting AMPK/mTOR/UNC-51-like kinase 1 (ULK-1) pathway in human glioma U251 and U87 cells [149]. In contrast, berberine induces protective autophagy in human malignant pleural mesothelioma NCI-H2452 cells, and inhibition of autophagy promotes berberine-induced apoptosis [150]. Therefore, autophagy plays a dual role in berberine-induced apoptosis.…”
Section: Berberinementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, berberine can induce autophagic cancer cell death through increased GRP78 levels and enhancing the binding ability of GRP78 to VPS34 in human colorectal cancer HCT-116 cells [148], whilst it induces autophagy through inhibiting AMPK/mTOR/UNC-51-like kinase 1 (ULK-1) pathway in human glioma U251 and U87 cells [149]. In contrast, berberine induces protective autophagy in human malignant pleural mesothelioma NCI-H2452 cells, and inhibition of autophagy promotes berberine-induced apoptosis [150]. Therefore, autophagy plays a dual role in berberine-induced apoptosis.…”
Section: Berberinementioning
confidence: 99%
“…Several mechanisms have been identified for the anti-proliferative effects of berberine, including down-regulation of cyclins A, D, cyclin-dependent kinase (CDK) 1, CDK4, MMP-2 and janus kinase 2 (Jak2)/vascular endothelial growth factor (VEGF)/NF-κB/activator protein 1 (AP-1) pathway, and induction of autophagic cell death via mTOR signaling pathway [149,155,156]. Berberine also induces mitochondrial-mediated apoptosis through the loss of mitochondrial membrane potential, cytochrome c release, caspase and PARP activation, up-regulation of pro-apoptotic Bcl-2 family proteins, and down-regulation of antiapoptotic Bcl-2 family proteins [150,[157][158][159]. It can also activate apoptosis-inducing factor to induce ROSmediated cell death in pancreatic, breast, and colon cancers [158,160,161].…”
Section: Berberinementioning
confidence: 99%
“…These findings suggest that induced apoptosis by BBR can occur in the NCI-H2452 human Malignant Pleural Mesothelioma (MPM) cells through the signaling of cytochrome c/caspase-9 and -3. 87 As demonstrated by the recent experiments, BBR exhibits cytotoxicity and induces apoptosis in human leukemia cells. For instance, an investigation revealed that in HL-60 and WEHI-3 Acute Myeloid Leukemia (AML) cell line, the apoptosis was induced by the activation of caspase-3 and depolarization of mitochondrial membrane by BBR treatment.…”
Section: Bbr Induces Apoptosismentioning
confidence: 92%
“…The results of the analysis of berberine-and matrine-induced apoptosis are shown in Figures 2 and 3. Co-incubation with berberine and matrine significantly increased apoptosis in HeLa and SiHa cells with apparent synergism (32)(33). The apoptosis rates (early plus late apoptosis) of HeLa and SiHa cells in the normal control samples were 2.0 ± 0.4% and 1.9 ± 0.4%, and those of berberine-treated HeLa and SiHa cells were 16.2 ± 1.5% and 18.9 ± 1.4%, respectively.…”
Section: Berberine and Matrine Promote Apoptosismentioning
confidence: 95%